The Effect of Work Environment and Communication on Employee Satisfaction of Employees at the Population Department and Civil Registration of Palembang City - Saskia Violita Elsa (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effects of work environment and communication on employees' job satisfaction at the Palembang City Population and Civil Registration Service. Data of 106 respondents were collected through a questionnaire and analyzed employing the multiple linear regression method. The results of the investigation exhibit that partially each of work environment and communication has a significant effect on job satisfaction. Likewise, work environment and communication simultaneously have a significant effect on job satisfaction. These empirical findings can be beneficial for the Palembang City Population and Civil Registration Service. The leader in this government agency should pay attention to the work environment and communication factors to optimize employees' job satisfaction.